Regime and Education A Study in the History of Political Philosophy - Dagg, Ian. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This volume is an inquiry into the history of political philosophy by way of the general theme of education. Each contributor addresses the relationship between a particular political philosopher's broad teaching on the best political order and that political philosopher's teaching about education. The unifying contention of the work is that each political philosopher considered in the volume promotes a certain kind of political regime and therefore a particular mode of education essential to that regime. Each chapter, written by a separate contributor, is distinguished from the others primarily by the political philosopher being considered. The book has a chapter dedicated to each of the following political philosophers: Plato, Xenophon, Aristotle, Machiavelli, Bacon, Locke, Rousseau, Tocqueville, and Nietzsche. The volume provides a survey of educational models by some of the greatest thinkers of the West, while continually demonstrating that the two themes of politics and education are inseparable. Ian Dagg is an Adjunct Professor at the University of Dallas and Baylor University, USA. He received a doctoral degree from the University of Dallas in Philosophic Studies in Politics. He has published "Natural Religion in Montesquieu's Persian Letters and The Spirit of the Laws" as well as a Review Essay of On the Happiness of the Philosophic Life by Heinrich Meier translated by Robert Berman in Interpretation: A Journal of Political Philosophy. His dissertation is Bad Beginnings, Failed Attempts to Control Convention, and Political Concessions: An Analysis of Plato's Laws.
1. Introduction (Ian Dagg) -- 2. The Limits of Regimes: Education and Character Formation in Xenophon's Political Thought (Gregory A. McBrayer) -- 3. The Beautiful and the False: An Introduction to Plato's Hippias (Alex Priou) -- 4. The Connection Between Moral Virtue and Politics in Aristotle's Ethics (John Hungerford) -- 5. Machiavelli's Revolutionary Classical Education (John Peterson) -- 6. Bacon's Transformation of Philosophy: An Introduction to the Education of Bacon (Ian Dagg) -- 7. John Locke's Approximate Regime (Cole Simmons) -- 8. Education and Regime in Rousseau's Social Contract (Ian Dagg) -- 9. Tocqueville's Defense of Aristocratic Literature (Antonio Sosa) -- 10. Nietzsche and Political Education (Michael Grenke).
Keywords: Political science; Political science -- Philosophy; Critical theory; Political science -- Study and teaching; Political Theory; Political Philosophy; Critical Theory; Political Education